LEGAL ANALYSIS REGARDING THE USE OF ABSOLUTE POWER OF ATTORNEY BY OFFICIALS MAKING LAND DEEDS IN DEEDS OF TRANSFER OF LAND RIGHTS - Glenaldi Julio Anindhita Panjaitan (Universitas Labuhanbatu, 2024)
In carrying out a legal action, an individual can delegate their authority to another person to handle specific affairs or to carry out specific matters namely through a Power of Attorney. However, there are certain actions not permitted by regulations and laws to be executed through a power of attorney, one of which is the absolute power to transfer land rights. A Deed of Sale and Purchase created by a Land Deed Official based on the use of absolute power can result in the deed being legally null and void and may lead to diputes in the future. The purpose of this research is to analyse the position of absolute power in deeds of land rights transfer made before a Land Deed Official. This research is juridical-normative, employing an explanatory research form, reinforcing the existing legal conditions to strengthen the application of legal theories and norms, and presenting the research findings in a descriptive report. The conclusion of this research is that the misuse of absolute power in the transfer of land rights still occurs frequently in practice, especially in matters of land rights transfer that are clearly prohibited by existing regulations and such abuse can result in the authentic deed made by the public official being legally void. This is due to the lack of precision by public officials in creating authentic deeds in accordance with the prevailing regulations. Keywords: Absolute Power, Land Deed Official, Transfer of Land Rights.